Legal Review of Ship Certification After the Issuance of Law Number 11 of 2020 Concerning Job Creation: Case Study of The Issuance of Fish Vessel Safety Certificates - Awwal, Farijs; Fahmal, A. Muin; Razak, Askari (Manunggal Halim Jaya, 2024)
This research examines the shift in authority and processes related to the certification of fishing vessels in Indonesia after the enactment of Law No. 11 of 2020 on Job Creation. The primary objective of this study is to analyze the legal force and implications of the transfer of authority from the Ministry of Transportation to the Ministry of Marine Affairs and Fisheries (KKP) in issuing fish vessel certifications. Using a normative juridical approach, this study investigates the procedural changes, challenges, and impacts of the new regulatory framework on fishing vessel safety and compliance. The findings show that the Job Creation Law simplifies licensing procedures while ensuring the safety and seaworthiness of fishing vessels. However, the study also highlights the challenges posed by a shortage of qualified inspectors, leading to delays in the certification process. This research underscores the need for regulatory adjustments and additional inspector training to align the maritime sector with the law’s goal of promoting safety and business efficiency.